Asuhan Keperawatan Pada Ny. T Dengan Gangguan Sistem Kardiovaskular: Congestive Heart Failure (CHF) Di Ruang Mawar 1 RSUD dr. Soeselo Kabupaten Tegal - Dila Ulhaq; Ahmad Zakiudin (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Introduction: Congestive Heart Failure (CHF) is a complex clinical syndrome caused by the inability of the heart to pump blood adequately to meet the body's metabolic demands. This condition may result in dyspnea, edema, activity intolerance, fatigue, and reduced quality of life. Comprehensive nursing care is essential to address patients' needs and improve health outcomes. Methods: This study employed a descriptive case study approach. Data were collected through interviews, observation, physical examination, and medical record review. Nursing care was provided using the nursing process, including assessment, nursing diagnosis, planning, implementation, and evaluation. Results: The assessment of Mrs. T identified four nursing diagnoses: ineffective breathing pattern, hypervolemia, activity intolerance, and knowledge deficit. Nursing interventions included semi-Fowler positioning, fluid balance monitoring, passive Range of Motion (ROM) exercises, and health education. Following two days of nursing implementation, three nursing diagnoses were resolved, namely ineffective breathing pattern, activity intolerance, and knowledge deficit. Hypervolemia was partially resolved due to persistent fluid imbalance. Discussion: The findings indicate that the application of systematic nursing care can improve several clinical problems experienced by CHF patients. However, fluid balance management remains a challenge, highlighting the importance of patient adherence to fluid restriction and continuous monitoring to prevent worsening symptoms.